2018
DOI: 10.1002/cbin.10954
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensis polysaccharide inhibits proliferation, migration, and invasion by downregulating microRNA‐675 in human neuroblastoma cell line SH‐SY5Y

Abstract: Neuroblastoma is the most common tumor diagnosed in children and infants, with high recurrence and poor prognosis. Angelica sinensis polysaccharide (AP) whose average molecular weight is 72,900 Da possesses various bioactivities. We aimed to explore the effects of AP on neuroblastoma SH-SY5Y cells as well as the underlying mechanisms. Effects of AP on cell viability, proliferation, apoptosis, migration, invasion, and expressions of long noncoding RNA H19 (lncRNA-H19), microRNA (miR)-675, and CD44 were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…However, a recent study also showed the inhibitory effects of AP on cell proliferation, migration, and invasion. 41 The results in our study are inconsistent with this study, possibly because of the different cell lines used and the different regulatory mechanisms in the experiments. Further studies are still needed in order to confirm these findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, a recent study also showed the inhibitory effects of AP on cell proliferation, migration, and invasion. 41 The results in our study are inconsistent with this study, possibly because of the different cell lines used and the different regulatory mechanisms in the experiments. Further studies are still needed in order to confirm these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The interesting results revealed that AP increased the expression level of H19 in a dose-dependent manner. However, Yang et al 41 found that expression of H19 was significantly downregulated in AP-treated neuroblastoma cells. Different expression levels of H19 might be due to different cell lines used in the studies.…”
Section: Discussionmentioning
confidence: 98%
“…Coincidentally, Bcl2/adenovirus EIB 19kD-interacting protein 3 (BNIP3) has been reported not only to exert key functions in neural precursor cells (NPCs) but also show potential roles in responding to hypoxiainduced injury [10]. In addition, as the previous literature reported that AP normally achieves its functions through regulating some other factors, such as miR-223 [7], miR-675 [11] and activating transcription factor 6 (ATF6) pathway [12]. Herein, is there possible regulating relationship between AP and BNIP3?…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in recent studies that polysaccharides from traditional Chinese medicine (TCM) can improve the immunosuppressive state of tumor microenvironment to play an antitumor effect [1], through regulating T lymphocyte subsets in the tumor microenvironment, promoting the maturation of dendritic cells (DC), activating macrophages, and inhibiting tumor angiogenesis. In our previous researches, it was found that Angelica polysaccharide (AP) could inhibit tumor growth and enhance antitumor immunity [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%